Request Strategies Used In Twilight Novel By Stephenie Meyer (A Pragmatics Approach) - Yulianto, Pradiyan Hendi; , Drs. Agus Wijayanto, MA, Ph. D.; , Dra. Siti Zuhriyah Ariatmi, M.Hum (2013)
This study focuses on analyzing the type of request strategy using the theory of request by Anna Trosborg. This study aim at 1) describing the type of request strategy found in Twilight, 2) clarifying pragma linguistic form found in the utterance of request in Twilight, and 3) describing the intention of request strategy found in Twilight. This research applies descriptive qualitative method. The data are a novel by Stephenie Meyer entitled "Twilight". The way to collect data is using docummentation method. The data analyzed are request strategies found in the novel "Twilight" and combines by describing pragma linguistic form: dwongraders and upgraders. The result show that 1) there are 10.86 % or 19 data of hints, 12.57 % or 22 data of ability/willingness, 6.29 % or 11 data of suggetory formulae, 9.14 % or 16 data of wishes/desires, 7.43 % or 13 data of needs/demands, 14.86 % or 26 data of obligations/necessity, 17.14 % or 30 data of performatives, and 21.74 % or 38 data of imperatives and 2) there are found 3 pragma linguistic form, namely downgraders, upgraders, and the other has no pragma linguistic form. The last is 3) the intention of request, there are anxiousness, hoping, clarifying, curiousness, suggestion, swearing, warning, panic, recommending, threatening, frightfulness, phatic and ordering.